Testbeam and laboratory test results of irradiated 3D CMS pixel detectors - Bubna, M; Alagoz, E; Cervantes, M; Krzywda, A; Arndt, K; Obertino, M; Solano, A; Dalla Betta, G; Menace, D; Moroni, L; Uplegger, L; Rivera, R; et al. (2013)
The CMS silicon pixel detector is the tracking device closest to the LHC p-p collisions, which precisely reconstructs the charged particle trajectories. The planar technology used in the current innermost layer of the pixel detector will reach the design limit for radiation hardness at the end of Phase I upgrade and will need to be replaced before the Phase II upgrade in 2020. Due to its unprecedented performance in harsh radiation environments, 3D silicon technology is under consideration as a possible replacement of planar technology for the High Luminosity-LHC or HL-LHC. 3D silicon detectors are fabricated by the Deep Reactive-Ion-Etching (DRIE) technique which allows p- and n-type electrodes to be processed through the silicon substrate as opposed to being implanted through the silicon surface. The 3D CMS pixel devices presented in this paper were processed at FBK. They were bump bonded to the current CMS pixel readout chip, tested in the laboratory, and testbeams carried out at FNAL with the proton beam of 120 GeV/c. In this paper we present the laboratory and beam test results for the irradiated 3D CMS pixel devices. © 2013.